Effect Of Green Tea Extract (Camelia Sinensis) Reduce Weight in Obesity Male Wistar Rats (Rattus Norvegicus) - Franata, Aji; Faridz Syahrian, Muhammad; Eldin, Eldin; Puspawani, Yeni (Sean Institute, 2023)
This study was to determine the effect of green tea extract (Camellia sinensis) in reducing body weight in obese male Wistar rats (Rattus norvegicus). Obesity is a condition of excessive accumulation of body fat so that a person's weight is far above normal and can endanger health. There was an effect of giving green tea leaf extract on weight loss in male Wistar rats at doses of 4.5 grams, 5.5 grams, and 6.5 grams before and after being given green tea leaf extract. The quantity of green tea extract of 6.5 grams was significantly lower than the other groups. The ingredients that have the most effect on weight loss are Epigallocatechin-3-gallate, L-theanine, and caffeine. So, it was concluded that green tea could be used to treat overweight and obesity because the content of green tea (Camellia sinensis) can reduce body weight and fat levels.